Simulating the induction heating of cross-ply C/PEKK laminates – sensitivity and effect of material variability. (3rd September 2021) - Grouve, Wouter J. B.; Sacchetti, Francisco; Vruggink, Evan J.; Akkerman, Remko
Abstract : A simulation model for the induction heating of UD tape-based thermoplastic composites is presented in this work. The model is based on the electrical ply properties which were determined experimentally for two commercially available carbon reinforced tape materials. Moreover, the interrelation between the measured electrical conductivities and the fiber distribution in the tape and laminates is discussed based on microscopic structure evaluation. The model was validated experimentally for the induction heating of cross-ply laminates. Subsequently, the effect of the experimental variability in the measured conductivities on the heating behavior was investigated using the simulation model. It was found that the material variability can have a significant effect on the heating behavior.